Translating ancient Greek drama in early modern Europe theory and practice (15th-16th centuries) - Bastin-Hammou, Malika 1972-; Di Martino, Giovanna; Dudouyt, Cécile 1981-; Jackson, Lucy 1986- (De Gruyter, 2023)
The volume brings together contributions on 15th and 16th century translation throughout Europe (in particular Italy, France, Spain, Portugal, Germany, and England).Whilst studies of the reception of ancient Greek drama in this period have generally focused on one national tradition, this book widens the geographical and linguistic scope so as to approach it as a European phenomenon. Latin translations are particularly emblematic of this broader scope: translators from all over Europe latinised Greek drama and, as they did so, developed networks of translators and practices of translation that could transcend national borders. The chapters collected here demonstrate that translation theory and practice did not develop in national isolation, but were part of a larger European phenomenon, nourished by common references to Biblical and Greco-Roman antiquities, and honed by common religious and scholarly controversies. In addition to situating these texts in the wider context of the reception of Greek drama in the early modern period, this volume opens avenues for theoretical debate about translation practices and discourses on translation, and on how they map on to twenty-first-century terminology
Aus der Danksagung: "This volume draws on the expertise of scholars from across the European continent and largely emerges from two conferences in particular: the first on Translating Greek Tragedy in 16th-century Europe, held at St Hilda's College (Oxford) on 14th December 2018; the second on Translating Greek Drama in 15th–16th century Europe, held at the Maison Française d'Oxford on 29th November 2019. Thanks go to both of these institutions and the other organisers' institutions for their sponsorship of both events."
Keywords: Geschichte 1480-1600; Europa; Frühe Neuzeit; Übersetzungstheorie; LITERARY CRITICISM / Ancient & Classical; Griechisch; Übersetzung; Drama; Konferenzschrift -- St Hilda's College -- 14.12.2018 -- Oxford; Konferenzschrift -- Maison Française -- 29.11.2019 -- Oxford